Space High-Voltage Power Module - Zhao, Wenjie; Jiang, Yuanyuan; Wu, Jianchao; Huang, Yonghui; Zhu, Yan; An, Junshe; Wan, Cheng-an (Frontiers in Energy Research, 2021)
With the rapid development of the world's aerospace technologies, a high-power and high-reliability space high-voltage power supply is significantly required by new generation of applications, including high-power electric propulsion, space welding, deep space exploration and space solar power stations. However, it is quite difficult for space power supplies to directly achieve high-voltage output from the bus, because of the harshness of the space environment and the performance limitations of existing aerospace-grade electronic components. This paper proposes a high-voltage power supply module design for space welding applications，which outputs 1kV and 200W when the input is 100V. This paper also improves the efficiency of the high-voltage converter with a phase-shifted full-bridge series resonant circuit, then simulates the optimized power module and the electric field distribution of the high-voltage circuit board.